Public Relations Management and Its Role in Shaping The Image of Islamic Educational Institutions in Responding to Community Needs - Syafri Fadillah Marpaung (MASI Mandiri Edukasi, 2026)
Islamic educational institutions often face challenges in building and maintaining a positive public image amid increasing competition and rising expectations from local communities. These challenges highlight the need for public relations (PR) management strategies that are not only effective in communication but also responsive to sociocultural contexts. This study aims to analyze the strategic role of public relations management in shaping a positive image of Islamic educational institutions based on local community needs. This research employed a qualitative approach using content analysis combined with a systematic literature review. Data were obtained from institutional documents, media content, and relevant scholarly sources. The findings indicate that the effectiveness of PR management is determined not merely by external communication activities, but by the alignment of PR strategies with the cultural and social values of the surrounding community. The integration of Islamic values and active community participation emerged as key differentiating factors in strengthening public trust. In addition to digital communication and media publication strategies, the study reveals that the involvement of religious leaders, the organization of religious forums, and the application of a humanist communication approach significantly contribute to enhancing institutional reputation. Overall, this study contributes to the development of educational public relations theory by emphasizing the importance of sociocultural and value-based approaches in designing sustainable institutional image strategies.